P1216EPIDEMIOLOGY OF HYPERTENSION IN PERITONEAL DIALYSIS USING CLINIC AND AMBULATORY BLOOD PRESSURE MONITORING. (6th June 2020) - Vaios, Vasilios; Georgianos, Panagiotis; Vareta, Georgia; Karpetas, Antonios; Ntounousi, Evangelia; Dimitriadis, Chrysostomos; Papagianni, Aikaterini; Zebekakis, Pantelis; Liakopoulos, Vassilios
Abstract: Background and Aims: Earlier studies that were based on routine clinic blood pressure (BP) recordings suggested that the prevalence of hypertension is lower in patients on peritoneal dialysis (PD) than in those receiving maintenance hemodialysis. These studies, however, did not incorporate the "gold-standard" method of ambulatory BP monitoring (ABPM). The aim of the present study was to quantify the prevalence and control of hypertension in a cohort of 81 peritoneal dialysis (PD) patients using clinic and ambulatory BP recordings. Method: Triplicate BP recordings were obtained after a 5-minute seated rest at clinic with the validated monitor HEM-705 CP (Omron, HealthCare). 24-hour ABPM was subsequently performed with the Mobil-O-Graph device (IEM, Germany). Hypertension was defined as (i) average clinic BP ≥140/90 mmHg or antihypertensive drug use and (ii) 24-hour BP ≥130/80 mmHg or current use of antihypertensive drugs. Results: The prevalence of hypertension was 92.6% with clinic BP recordings and 93.8 with ABPM. In all, 75 participants (92.6%) were receiving therapy with an average of 2.4 antihypertensive medications. The rates of adequate control of hypertension were 49.3% with the use of clinic BP recordings and 39.5% with ABPM, respectively. In all, 6.2% of participants were classified as normotensives, 33.3% had concordant control of hypertension with both techniques, 40.7% had concordant lack of control confirmed by both techniques, 5% had "white coat" hypertension and 14.8% had masked uncontrolled hypertension. Conclusion: This study suggests that the burden of hypertension among patients on PD is very high and that the wider use of ABPM is important to confirm the BP control status of these patients.